Application of multi-criteria optimization method for decision-making in the sphere financial support of the military troops - Artiushenko, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article considers the theoretical basis for the use of optimisation methods for managerial decision-making and search for an optimal solution. The article describes the methods of multi-criteria optimisation, which, based on the analysis of the relevant literature, are often used in various spheres of human activity, namely: simple additive weighting (SAW), elimination and choice expressing the reality (ELECTRE), preference ranking organisation method for enrichment evaluation (PROMETHEE), technique for order preference by similarity to ideal solution (TOPSIS), analytical hierarchy process (AHP), and analytical network process (ANP). The key characteristics of the decision-making environment in the field of military financial support are identified, based on the conditions and characteristics of such a decision-making environment, namely: a significant number of criteria to be taken into account, the presence of subjectivity in decision-making and the efficiency of such decisions, TOPSIS was chosen as the main method. In the methodological part of the article, the main characteristics, procedure of use and indicators of this method are considered. For practical application of the method, the article develops a case of decision-making by the military organisation A0001 regarding the optimal use of a limited financial resource out of 4 proposed options. In the article, a list of criteria was compiled, they were grouped, and a matrix was formed. In the final part of the article, a matrix of weighting coefficients for each of the 4 options is formed, its normalisation is carried out and the distance/closeness of the proposals of further solutions to the ideal solution is calculated. Based on the calculations, the author chose the optimal option for the use of financial resources, which, according to the TOPSIS method, had the smallest distance to the ideal solution, i.e., was the closest of the proposed options to the ideal option for the use of financial resources.
Keywords: budget, defense expediture, TOPSIS, multi-criteria optimization, making optimal management decisions, effectiveness of government expenditure